Diversity across the disciplines : research on people, policy, process, and paradigm - Murrell, Audrey J.; Petrie, Jennifer; Soudi, Abdesalam (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"Diversity research and scholarship has evolved over the past several decades and is now reaching a critical juncture. While the scholarship on diversity and inclusion has advanced within various disciplines and sub-disciplines, there have been limited conversations and collaborations across distinct areas of research. Theories, paradigms, research models and methodologies have evolved but continue to remain locked within specific area, disciplines, or theoretical canons. This collaborative edited volume examines diversity across disciplines in higher education. Our proposed book brings together contributions from the arts, sciences, and professional fields. In order to advance diversity and inclusion across campuses, multiple disciplinary perspectives need to be acknowledged and considered broadly. The current higher education climate necessitates multicultural and interdisciplinary collaboration. Global partnerships and technological advances require faculty, administrators, and graduate students to reach beyond their disciplinary focus to achieve successful programs and research projects. We need to become more familiar discussing diversity across disciplines. Our proposed book investigates diversity across disciplines with attention to people, process, policies, and paradigms. The four thematic categories of people, process, policies, and paradigms describe the multidisciplinary nature of diversity and topics relevant to faculty, administrators, and students in higher education. The framework provides a structure to understand the ways in which people are impacted by diversity and the complicated process of engaging with diversity in a variety of contexts. Policies draw attention to the dynamic nature of diversity across disciplines and paradigms presents models of diversity in research and education"--